Determinants of Sugar Imports, Sugar Consumption and Production in Indonesia (2000 – 2019 Study Case) - Al Azam, Nasrudin Ahmad; Antriyandarti, Ernoiz; Adi, Raden Kunto (Universitas Ahmad Dahlan, 2023)
Indonesia was a prime sugar exporter country in the past, but since year 1967 has been importing sugar from other countries. Sugar import volume has been increasing every year so Indonesia has become second largest sugar importer in the recent years. Based on those problems, this research aims to analyze the factors that affect Indonesian sugar imports. The data used for analysis is secondary data in the form of time series in the range of 20 years (2000 – 2019), which were collected from various related agencies. Data analysis uses Seemingly Unrelated Regression (SUR), which was used to analyze the effect of sugar production, GDP, sugar consumption, domestic sugar prices, International sugar prices, and rupiah exchange rate on the volume of Indonesian sugar imports. The result shows that only sugar consumption affects significantly sugar imports, while sugar production, GDP, domestic sugar prices, international sugar prices, and the rupiah exchange rate do not significantly affect sugar imports. Sugar consumption is affected by GDP and domestic sugar prices, while sugar production is affected by domestic sugar prices. In addition, sugar imports volume shows that trend imports grew positively with an estimated trend of 197.978 tons per year in the 2000 – 2019 period. According to the sugar import trend, can be concluded that there will be growth of sugar import volume in the coming years. Based on SUR analysis, sugar imports growth is caused by consumption growth and consumption growth is affected by the growth of GDP and the decrease in domestic sugar prices. One policy that can be implemented by the government to resolve the sugar import problems is the policy on sugar prices, because high sugar prices decrease sugar consumption, and on the other hand also increase domestic sugar production.